Democratization and development The case of Quinabut-an Irrigatiors Association. - Cabañezas, Vicente D. (Vicente D. Cabañezas, 2009)
This study is about a particular irrigators association. This study aimed to examine this cooperative in the context of democratization and development. Given the situation of the research subject and in consideration to the research locale, this will elevate a primary level organization into the realm of national cooperativism, democratization, and development.